A política social na produção do conhecimento do Serviço Social: estado da arte das dissertações de mestrado - Santos, Angela Kaline da Silva (2022)
The present Academic Master's is classified with investigative process developed in the Master's of the Postgraduate Program in Social Work at the Federal University of Paraíba. It presents with object of study the production of knowledge generated by the Social Work on Social Policy. It objectifies to analyze Master's Dissertations linked to the area of Social Policy, defended at PPGSS/UFPB from 2010 to 2019. This investigative analysis will be contextualized from the crisis of late bourgeois society in order to verify the inflections of this crisis in the production of Social Work's knowledge of Social Policy in the light of the hegemony of the Modernity Project from a Marxist critical perspective and the post-modern offensive. The debate on Social Work and Social Policy in Brazil expanded and became more dense throughout the 1980s and 1990s, consolidating itself in the 21st century. From this context, a broad process of construction of knowledge on Social Policy was established within the scope of the profession, being one of the basic pillars in the consolidation of Social Work as an area of knowledge, recognized by the agencies that promote research and post-graduate studies with an area of Applied Social Sciences. With research hypothesis, it is formulated that: the influence of the legacy of the Modernity Project in the critical-dialectical perspective in the Master's Dissertations in the area of Social Policy of the PPGSS/UFPB, derived from the Marxian and Marxist legacy, is hegemonic in the production of knowledge of Social Work, although the post-modern offensive in recent years is recognized. A historical-dialectical materialist theoretical-methodological perspective is adopted, determined in the contradictory social relations of late-bourgeois society. Methodologically, it is characterized as a bibliographical and documentary research using the state of the art for analytical mapping of trends that permeate the universe of 119 Master's Dissertations from PPGSS/UFPB, linked to the area of Social Policy. For this purpose, instruments and quanti-qualitative techniques of data collection and analysis are used. In the operationalization of the state of the art, we opted for the use of bibliographic indicators: areas of knowledge; thematic and authorial categories. Around the 171 master's dissertations defended between 2010 and 2019, there is a prevalence of the Social Policy area with 119 (70%) are linked to the area, to the detriment of the Theoretical-Practical Foundation of Social Work area with 52 (30 %) of dissertations defended. In conclusive terms, it appears that the production of knowledge generated on Social Policy generated by the PPGSS/UFPB is supported by the theoretical-methodological direction of the Marxist legacy, however, an incidence, even though still fragile, of specific aspects of postmodernity was identified expressed by the theoretical eclecticisms with the uncritical use of authors from different theoretical paradigms and secondaryization of methodology scientific indicated by 10% (16) of dissertations that don’t describe the type of research, and 33% (35) that don’t describe the method. This finding affects the affirmation of the hypothesis formulated in this research.